Association between epidermal growth factor receptor gene mutation status and short‑term efficacy of first‑line platinum‑containing chemotherapy in advanced non‑small cell lung cancer. Issue 1 (2022) - CHEN, LIN; QI, QIUFENG; ZHU, MING; ,; ZHANG, YAPING; ,; , YUN PENG; LIU, YONGPING
No abstract available